Whole‐body MRI‐DWI for assessment of residual disease after completion of therapy in lymphoma: A prospective multicenter study. Issue 6 (8th May 2015) - Littooij, Annemieke S.; Kwee, Thomas C.; de Keizer, Bart; Bruin, Marrie C.A.; Coma, Ana; Beek, Frederik J.A.; Fijnheer, Rob; Nievelstein, Rutger A.J.
Abstract : Background: To assess the performance of whole‐body MRI including diffusion‐weighted imaging (whole‐body MRI‐DWI) for the detection of residual disease after completion of treatment in lymphoma patients. Methods: Twenty‐six patients with lymphoma prospectively underwent whole‐body MRI‐DWI (1.5 Tesla MR) and 18F‐fluoro‐2‐deoxy‐D‐glucose positron emission tomography (FDG‐PET)/computed tomography (CT) for posttreatment evaluation which were visually assessed. Apparent diffusion coefficient (ADC) and FDG‐PET/CT standardized uptake value measurements were performed in all residual lesions. An unblinded expert panel reviewed all cases and determined the presence or absence of posttreatment residual disease using all available imaging (except for whole‐body MRI‐DWI), clinical, and histopathological information with a follow‐up of at least 6 months. The performance of whole‐body MRI‐DWI was compared with this panel reference standard. Results: Five of 26 patients were diagnosed with residual disease. Sensitivity and specificity for detection of residual disease with whole‐body MRI‐DWI were 100% and 62%, respectively. By ROC analysis, the optimal threshold of ADC was 1.21 × 10 −3 mm 2 /s with sensitivity and specificity of 100% and 91.7%, respectively. Conclusion: Our initial results suggest that visual whole‐body MRI‐DWI analysis has a very good sensitivity for detecting viable residual lesions after completion of therapy but lacks specificity. ADC measurements could potentially increase the specificity of whole‐body MRI. J. MAGN. RESON. IMAGING 2015;42:1646–1655.